Pametne tehnologije v izobraževanju medicinskih sester - Hvalič Touzery, Simona (Obzornik zdravstvene nege, 2023)
Introduction: Nursing, the nursing profession, and nursing education are all directly impacted by the development and advancement of the use of technology in healthcare. A lack of technical expertise among nurses poses a challenge to the quality of nursing and the quality of life of patients. The aim of the study was to determine to what extent the content related to smart technologies is included in the higher education of future nurses in Slovenia. Methods: The collection of the course syllabi was conducted in January and February 2023 by means of researching the websites of eight higher education institutions and personal contact with these faculties and head lecturers of individual subjects. We analyzed 20 course syllabi that met the inclusion criteria. A qualitative exploratory research design with content analysis and visualisation method was used. Results: Based on course syllabi we identified six content areas in the field of informatics, and information and communications technology (ICT): smart technologies, informatics and ICT basics, ICT in health education, ICT in health care, e-health, and other ICT-related topics. Smart technologies are rarely included in first- and second-cycle nursing education courses. Discussion and conclusion: Smart technologies are rarely included in the curricula of nursing courses at Slovenian higher education institutions. Given the rapid advancement of digitalization in health care and the important role of nurses in introducing and implementing these technologies in clinical practice, it would be necessary to ensure that nursing students and future nurses have up-to-date skills at a higher level of complexity.
Keywords: formalno izobraževanje; socialna robotika; Telemedicina; teleoskrba; Zdravstvena nega